Comparison of Oxidant/Antioxidant, Detoxification Systems in Various Tissue Homogenates and Mitochondria of Rats with Diabetes Induced by Streptozocin. (28th March 2012) - Çelık, Veysel Kenan; Şahın, Zeynep Deniz; Sari, İsmail and Bakir, Sevtap
Abstract : Objective . Oxidative stress is considered to be the main factor in the development of diabetic complications and tissue injury. our objective was to investigate and compare the oxidant/antioxidant conditions and detoxification mechanisms of the liver, lung, kidney, cardiac tissues, and mitochondria of rats with diabetes induced by streptozocin (STZ). Methods . Rats with diabetes induced by streptozocin were anesthetized by administering 90 mg/kg ketamine hydrochloride and 3 mg/kg xylazine hydrochloride. Thoracic cavities were incised open; liver, lung, kidney, and cardiac tissues were removed and stored at − 70 ° C. All samples were homogenized and mitochondrial fractions were separated. Total Antioxidant Status (TAS), Total Oxidant Status (TOS), Oxidative Stress Index (OSI), Paraoxonase (PON), Arylesterase, Catalase (Cat), Malondialdehyde (MDA), and Glutathion-S-transferase were measured in each fraction. Results . MDA and TOS levels were significantly increased in liver tissues, and T OS and OSI were increased in the mitochondrial fractions of diabetic rats. These increases were not statistically significant compared to the control group. No significant differences were determined in the antioxidant and GST activities. Conclusion . According to our results, oxidative stress has not developed in rats with diabetes induced by streptozocin. The detoxification system was induced; however, this induction did not differ significantly from the controls.